Isolation and Characterization of Potential Lignocellulosic Degrading Bacteria From chicken Manure Compost - Zhafira Tiza Maesharoh Soleman; Feky Mantiri; Marhaenus Rumondor (JURNAL BIOS LOGOS, 2023)
Lignocellulose is the main component that can be found in plants. Lignocellulose consists of three components, namely hemicellulose, lignin, and cellulose. The maximum utilization of lignocellulose cannot be carried out without being degraded, however there are difficulties in carrying out the degradation. The difficulty faced in the degradation process is the presence of lignin components that provide strength and stiffness to the plant, which make it is quite resistant to the degradation process. Lignocellulose degradation requires delignification. The delignification process can be facilitated by enzymes produced by a number of microorganisms, including bacteria can produce lignocellulosic enzymes. This study aims to isolate and characterize lignocellulose-degrading bacteria in chicken manure, and to assess the ability of bacteria to degrade lignocellulose. The results obtained from this research showed that an isolate which has high similarity with Shigella flexneri bacteria which was found in chicken manure and exhibits a potential to degrade lignocellulose.